La aplicación de la teoría de la imputación objetiva en el delito de estafa en el Ecuador. - Jácome, Andrés I. (2022)
Despite being an old institution, the influence of the theory of objective imputation has become very relevant for criminal law today. Principles such as the creation of the impermissible risk and the imputation of the result are the starting point for the correct normative imputation of crimes. For the crime of fraud, this is essential; however, in the light of its criminal evolution, the elements described are not sufficient to attribute in a timely manner, the disapproved result to the impermissible conduct of a subject. At this point, the theory of imputation offers a solution through the use of certain principles, which better deepen the imputation problems posed by the vast criminal model of fraud. This is precisely the main objective of this research: To expose the relevance and usefulness of the Theory of Objective Imputation in the crime of swindling typified in the COIP. Based on the above, this article analyzes the typical elements of fraud, such as deceit, error, patrimonial disposition and prejudice and their relationship with self-endangerment, consent, avoidability, unpredictability and normative scope. The methodological approach is quantitative, the main instrument is the interview with experts knowledgeable on the subject who express the applicability, benefits and disadvantages that could arise in the use of objective imputation in the crime of fraud.